Developing Student Character Education Through Islamic Boarding School Culture In Islamic Elementary Schools - Ahmad Shiddiq; Nurul Ulfatin; Ali Imron; Arifin Imron (AL-ISHLAH: Jurnal Pendidikan, 2024)
Many problems occur in the world of education, especially moral (character) crises among students, some of which are violence between students, promiscuity, free sex, and drugs. School participation is really needed to deal with the problems that occur, and teachers are the main spearheads in the process of forming student character at school. This research aims to develop character education through Islamic boarding school culture in Islamic elementary schools. This type of research is qualitative research using a phenomenological approach with the aim of describing, understanding, and interpreting the phenomena that occur. This research was conducted at an Islamic school located on Sumenep Island. The reason the researcher conducted research at an Islamic elementary school was that this school was unique in implementing Islamic boarding school culture into the school environment. The research subjects used a purposive sampling technique because the target informants met the research objective criteria. The informants in this research were school principals, religious teachers, and students. Data collection techniques in this research used semi-structured interviews and non-participant observation. Data analysis in this research uses Miles and Huberman's theory, which includes data collection, data consolidation, data display, and drawing conclusions or data verification. The research results show that Islamic boarding schools are one of the educational institutions in Indonesia that contribute to developing the character of students in the form of culture and can be applied at the elementary, middle, and high school levels by internalizing the process of instilling attitudes within oneself through coaching and guidance. Additionally, development.